Good at Heart: Developing a Tertiary Perinatal Cardiac Service; the First Eight Years of Experience. Issue 3 (September 2021) - Heland, S.; de Chellis, A.; Rieder, W.; Sleeman, M.; Johns, J.; Lancefield, T.; Robinson, A.; Fung, A.; Walker, S.
Abstract : ( Aust N Z J Obstet Gynaecol . 2020;60:760–765) Improved obstetric care in high income countries has reduced overall maternal mortality and morbidity, but an increasing trend of cardiac disease contribution to adverse maternal outcomes has emerged. In developed countries, cardiac disease is now the most common cause of indirect maternal death. In 2009, Mercy Hospital for Women created a multidisciplinary perinatal cardiac service to improve outcomes in parturients with congenital and acquired cardiac disease. This study describes outcomes after the first 8 years of that service and summarizes potential needs of tertiary care related to the significant risks that maternal heart disease poses to fetal and maternal well-being.